2013
DOI: 10.1063/1.4802602
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of die drool sample produced by HDPE melt extrusion

Abstract: Abstract. In this work, flow induced molecular weight fractionation experiment was performed for HDPE polymer on specially designed laboratory extrusion setup. Die drool sample, accumulated at the die exit face, together with virgin pellets were consequently characterized experimentally by gel permeable chromatography, differential scanning calorimetry and rheology as well as theoretically by recently proposed generalized Newtonian model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Besides, our works focused on flow induced molecular weight fractionation and die drool during HDPE melt extrusion 28,[38][39][40][41]45,57,84,[148][149][150][151]171 presented in more detail in other parts of the text, in a recently published contribution 40 two linear unfilled HDPEs differing in a small amount of high molecular weight species only were investigated. With the aid of the GPC technique, it was found that first, the content of long chains in the drool sample produced by more elastic HDPE containing high molecular weight species is smaller in comparison with the drool sample produced by less elastic HDPE free of high molecular weight species.…”
Section: Flow-induced Molecular Weight Fractionation Theorymentioning
confidence: 99%
“…Besides, our works focused on flow induced molecular weight fractionation and die drool during HDPE melt extrusion 28,[38][39][40][41]45,57,84,[148][149][150][151]171 presented in more detail in other parts of the text, in a recently published contribution 40 two linear unfilled HDPEs differing in a small amount of high molecular weight species only were investigated. With the aid of the GPC technique, it was found that first, the content of long chains in the drool sample produced by more elastic HDPE containing high molecular weight species is smaller in comparison with the drool sample produced by less elastic HDPE free of high molecular weight species.…”
Section: Flow-induced Molecular Weight Fractionation Theorymentioning
confidence: 99%
“…For the pure shear flow, the function f ( I |D| , II D , III D ) becomes equal to 1 and thus, the viscosity becomes a function of second invariant of deformation rate tensor D (IID=sans-serifγ˙2) only. In the pure uniaxial extensional flow, where I|D|= 2trueε˙, IID=3sans-serifε˙2, and IIID=sans-serifε˙3/4, the function f ( I |D| , II D , III D ) becomes nonzero and model becomes capable of representing steady-state extensional flows for different polymer melts [69,70,71,72,73,74].…”
Section: Theoreticalmentioning
confidence: 99%